SOSIOLOGI PENDIDIKAN DALAM MEMBENTUK KARAKTER SEORANG ANAK - Indriani Indriani (CV. ADIBA AISHA AMIRA, 2024)
This article explains the role of sociological education in shaping a child's character. The science of sociology is very complex in explaining social phenomena in society or individuals in the process of socialization. A child's character will be influenced by education and norms in society. So that sociological education plays a very important role in forming the character of an individual, group and society. This research uses a qualitative approach with a library study research method and research data sourced from literature, journals, etc book. In this method all data obtained will be analyzed to reach conclusions. The results of this research will show that educational sociology as a branch of sociology plays an important role in forming the character of students at school.